Preparedness and containment of Ebola virus during football competitions in the southwestern, Nigeria (2018)
Objective: The Ebola virus disease, formerly called the Ebola haemorrhagic fever, was first identified in rural Zaire (now the Democratic Republic of Congo) in 1976, where it killed 280 people. The disease had mostly been confined to relatively small outbreaks in rural settings, until the 2014 outbreak, which hit urban areas in Liberia, Sierra Leone, and Guinea. Today, the African countries affected by the outbreak of Ebola in 2014 have been able to curtail it and have even come out strong out of its devastating effect. However, this disease has a tricky way of sneaking back, as it has demonstrated in the time past. So to what extent is our stadium equipped to screen, detect, prevent and contain Ebola spread during football competitions. This has been the major focus of this research Methods: Descriptive survey research design was used for the study. It was correlational type which explores the relationships that exists among variables on which predictions are made based on the relationships. A total of 75 (Seventy five) respondents were selected from among the Sport medical personnel, coaches, athletes, sport managers/administrators and sport journalist from each stadium to make a total of 150 (one hundred and fifty) respondents. A self-developed questionnaire which has reliability coefficient of 0.87 was used to collect data while the data were analysed using inferential statistics of chi-square at 0.05 level of significance. Results: The findings of the study reveal that the selected stadia lack surveillance and detection capabilities for Ebola and other infectious diseases. It was also discovered that many personnel working in and around the stadia, athletes and spectators lack adequate knowledge about Ebola. The health facilities in around the complex too did not have functional diagnostic and containment capabilities for Ebola. Conclusions: It was concluded among others that adequate laboratory service and active surveillance capacity for Ebola detection during football competition should always be made available by the authority concern.